2021
DOI: 10.3390/microorganisms9050961
|View full text |Cite
|
Sign up to set email alerts
|

Shift of Dominant Species in Plant Community and Soil Chemical Properties Shape Soil Bacterial Community Characteristics and Putative Functions: A Case Study on Topographic Variation in a Mountain Pasture

Abstract: Reducing management intensity according to the topography of pastures can change the dominant plant species from sown forages to weeds. It is unclear how changes in species dominance in plant community drive spatial variation in soil bacterial community characteristics and functions in association with edaphic condition. Analysing separately the effects of both plant communities and soil chemical properties on bacterial community is crucial for understanding the biogeographic process at a small scale. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Our results showed that the dominant species were in the plant–bacterial networks, and most dominant plant species also were keystone species (Figure 3, Table S1). Actually, dominant plant species as locally abundant affected community structure and ecosystem function (Avolio et al, 2019), which shaped soil bacterial community (Eo et al, 2021; Wang et al, 2018). Moreover, we discovered that some species with low numbers were also identified as keystone species.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the dominant species were in the plant–bacterial networks, and most dominant plant species also were keystone species (Figure 3, Table S1). Actually, dominant plant species as locally abundant affected community structure and ecosystem function (Avolio et al, 2019), which shaped soil bacterial community (Eo et al, 2021; Wang et al, 2018). Moreover, we discovered that some species with low numbers were also identified as keystone species.…”
Section: Discussionmentioning
confidence: 99%